Post-operative Analgesic Requirement in Non-closure and Closure of Peritoneum during Open Appendectomy: A Randomized Controlled Study - BASARKOD SURESH; AMBI UDAY S; GANESHNAVAR ANILKUMAR; EMMI SHAILESH; LAMANI Y P (Journal of Clinical and Diagnostic Research, 2012)
Objectives: To assess the post-operative analgesic requirement of non-closure of the visceral and parietal peritoneum at open appendectomy as compared to suture peritonization. Design: A randomized double-blind controlled trail was performed on 100 patients who underwent open appendectomy. Main outcome measures: Post-operative pain scores as assessed by visual analogue scale and analgesic requirement. Results: Pain scores at 24 hours were less in non-closure than closure group and analgesic requirement was significantly lesser in non-closure than closure group after 24 hours. Conclusion: In conclusion, not suturing the peritoneum at the appendectomy has beneficial effects on post-operative pain and we also emphasise the absence of short term morbidity when peritoneum is not closed. Therefore we recommend the non-closure of peritoneum at appendectomy.